The gift : creativity and the artist in the modern world - Hyde, Lewis, 1945- (New York : Vintage Books, 2007)
Examines the concept of gifts in anthropological terms and uses this approach to analyze the situation of creative artists and their gifts to society
Includes index
Includes bibliographical references (p.[387]-391) and index
Keywords: Gifts; Creation (Literary, artistic, etc.); Economic anthropology; Art and society